(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article is devoted to the research of the features of marketing of products of non-waste agricultural production, which include food products, feed and feed additives, organic fertilizers, alternative energy sources, products for technical purposes. It is established that marketing is a means of implementing the strategy of non-waste agro-industrial enterprises that allows them to adapt to dynamic changes in the external environment, to provide competitive advantages in the economic sphere, to meet the specific needs and demands of consumers, to form a positive attitude towards agro-industrial products of non-waste production and producers. The main directions of marketing activity in the sphere of non-waste agro-industrial production are studied: a comprehensive study of the state of the agro-industrial products market of non-waste technological systems and prospects for its development with the purpose of identifying and assessing the existing and potential demand of consumers for products of non-waste agro-industrial production and services; formation of demand and promotion of the sale of products of non-waste agro-industrial production; choice of means of communicative politics; the development of a system of prices for products of non-waste agro-industrial production; organization of methods of commodity circulation of products of non-waste agro-industrial production, management of commodity assortment; checking effectiveness, improving and monitoring the effectiveness of marketing activities. It is proved that marketing of products of non-waste agro-industrial production is a complex and multifaceted activity aimed at organizing the production of non-waste production of the agro-industrial complex to the consumer in order to satisfy the interests of consumers who receive high-quality products, producers who receive income and occupy a corresponding niche in the domestic and world markets and state interests by ensuring food security and integration into the international economic space